TARIX FANI MASHG‘ULOTLARIDA O‘QUVCHILARNI TO‘G‘RI VA MANTIQLI JAVOB BERISHGA O‘RGATISH USULLARI - Yerjanova, G.M. (SCIENCE and SOCIETY, 2022)
The article teaches students to answer questions correctly and logically in history lessons, not to give the student ready knowledge, but to encourage him to search, to find and analyze the data itself to do, to teach students knowledge and skills such as how to work with data, how and where to search for data, how to compare, what to compare.
Keywords: correct questioning; logical answer; national history; teaching methods; independent work; search; comparison; contract; ancestral history; national pride